Four new species and first nominal record of Chasmogenus Sharp, 1882 (Coleoptera: Hydrophilidae) from Brazil - Clarkson, Bruno; Ferreira-Jr, Nelson (Zootaxa, 2014)
The genus Chasmogenus Sharp, 1882 (Hydrophilidae: Acidocerinae) is recorded from Brazil for the first time. Four new species are described and illustrated from the Southeastern Region of the country: C. fluminensis sp. nov. (Rio de Janeiro State), C. lilianae sp. nov. (Rio de Janeiro State), C. itatiaia sp. nov. (Minas Gerais and Rio de Janeiro States), and C. ubatuba sp. nov. (São Paulo State). Chasmogenus sapucay Fernández, 1986 is recorded for the first time from Northern and Southeastern Brazil. Notes on morphology and an updated key for the South American species are provided.